The case for foreign electoral subversion - Fabre, C (Cambridge University Press, 2018)
It is widely alleged that President Putin's regime attempted to exercise influence on the 2016 U.S. presidential election. It is known that its Soviet predecessors funded Western communist parties for decades as a means to undermine noncommunist regimes. Similarly, the United States has a long history of interfering in the institutions and elections of its Latin American neighbors, as well as (at the height of the Cold War) its European allies. More recently, many believe that, absent U.S.-driven assistance, the Democratic Opposition of Serbia would have lost the 2000 Yugoslavian presidential election to Slobodan Milošević. As those examples suggest, attempting to subvert the democratic elections of a putatively sovereign country is a time-honored way of bending the latter's domestic and foreign policy to one's will. In this paper, I focus on the state-sponsored, nonviolent, nonkinetic subversion of nationwide elections (for short, subversion) through campaign and party financing, tampering with electoral registers, and conducting disinformation campaigns about candidates. I argue that, under certain conditions and subject to certain constraints, subversion is pro tanto justified as a means to prevent or end large-scale human rights violations.